An uncalled guest in the nose: a living leech - Belaldavar, Basavaraj P.; Umesh, Nagalotimath; Mohit, Sinha; Kalakuntla, Mounika (International Journal Of Community Medicine And Public Health, 2016)
Foreign bodies in the nasal cavity are commonly encountered as a cause of epistaxis; especially in children. Leeches are most common parasite found in hilly areas in India, particularly in rainy season.  However, nasal leech infestation (animate foreign body) as a cause of unilateral persistent epistaxis is very rare. We, herein present a case of nasal hirudiniasis in a 30 year old female. She presented with history of recurrent epistaxis with moving sensation and itching in the left nose.  Examination of nose showed a moving fleshy mass, which was a leech and was removed with a Luc’s forceps In developing countries, leech infestation as a cause of epistaxis should be suspected in patients with lower socioeconomic status or in those living in leech predominant areas, rural areas who give history of drinking polluted water from, or bathing in, stagnant ponds and puddles.